Pollen of the restinga vegetation of Algodoal/Maiandeua, Pará, Brazil. III. Polygalaceae and Polygonaceae - Lucas, Flávia Cristina Araújo; Carreira, Léa Maria Medeiros; Gurgel, Ely Simone Cajueiro; Gama, Thália do Socorro Serra (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
This study deals on pollen morphology of Polygalaceae and Polygonaceae in the Algodoal/Maiandeua island (coast of Pará State, Brazil), represented, respectively, by the species Polygala adenophora DC., P. monticola Kunth, P. spectabilis DC., P. variabilis Kunth, Coccoloba latifolia Lam., and C. ramosissima Wedd. Pollen grains from flower buttons, obtained from herbarium specimens, were acetholysed, described, measured, and photomicrographed under optical and scanning electron microscope. In the pollen grains of Polygalaceae, the size varies from medium to large, the shape from subprolate to prolate spheroidal, 9 (-10) (-13) (-16)-colporate, psilated to perforate sexine. Polygonaceae shows pollen grains prolate, tricolporate, and microreticulate sexine. An identification key based on exine ornamentation of the pollen of the studied species is given.